2009
DOI: 10.1093/rheumatology/kep170
|View full text |Cite
|
Sign up to set email alerts
|

Depression in RA patients treated with anti-TNF is common and under-recognized in the rheumatology clinic

Abstract: Depression is common but under-recognized in RA patients starting on anti-TNF therapy. Patients with persistent depression tended to respond less well to anti-TNF, with smaller reductions in DAS28. Given that a significant reduction in DAS28 is a requirement for continuing therapy, recognition and appropriate management of depression may improve TNF effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
87
4
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 14 publications
5
87
4
4
Order By: Relevance
“…Since cytokines play a pivotal role in the synovial inflammation in RA and TNF blockers exert strong therapeutic effects, it may be suggested that the cytokine -brain connection is essential in depression in RA. The hypothesis is supported by the observation of persistence of depression in patients with poor disease control by TNF blockers (Hider et al, 2009). However, studies investigating an association between depression in RA and increased CRP have yielded conflicting findings (Margaretten et al, 2011).…”
Section: Rheumatoid Arthritis and Depression-like Symptomsmentioning
confidence: 90%
“…Since cytokines play a pivotal role in the synovial inflammation in RA and TNF blockers exert strong therapeutic effects, it may be suggested that the cytokine -brain connection is essential in depression in RA. The hypothesis is supported by the observation of persistence of depression in patients with poor disease control by TNF blockers (Hider et al, 2009). However, studies investigating an association between depression in RA and increased CRP have yielded conflicting findings (Margaretten et al, 2011).…”
Section: Rheumatoid Arthritis and Depression-like Symptomsmentioning
confidence: 90%
“…As outlined above, there is abundant reason to assume that depression may actually change the disease and its impact on the patient. Cross-sectional studies provide conflicting results, with most describing an association between depressed mood and objective measures of disease activity, such as CRP and ESR [6,11,81,129,130]; however, others do not find such associations [131,132]. Some authors have found that anxiety does not correlate with ESR or CRP in RA patients [10,133], whereas others show that anxiety and disease activity were positively associated when measured simultaneously and 6 months apart [6].…”
Section: The Das Score and Its Componentsmentioning
confidence: 99%
“…RA patients exhibit deficits in cognitive function (learning and memory) [24] as well as increased anxiety [25] and depression [26]. The cognitive deficits observed in RA patients could be attributed to the high levels of pro-inflammatory cytokine TNF-α in serum [25,27].…”
mentioning
confidence: 99%